Familial Abdominal and Intestinal Lipomatosis Presenting with Upper GI Bleeding - Yilmaz Bilgic; Hasan Baki Altinsoy; Nezahat Yildirim; Ozkan Alatas; Burhan Hakan Kanat; Abdurrahman Sahin (Case Reports in Gastrointestinal Medicine)
Although lipomas are encapsulated benign tumors, systemic lipomatosis defines infiltrative nonencapsulated tumors resembling normal adipose tissue. Abdominal lipomatosis and intestinal lipomatosis are different clinicopathological entities with similar clinical symptoms. We describe here a case presenting with upper gastrointestinal bleeding from eroded submucosal lipoma at duodenum secondary to intestinal lipomatosis and abdominal lipomatosis.